Metabolism and urinary excretion kinetics of 2,4-di-tert-butylphenol after a single oral dose: Characterisation of suitable exposure biomarkers for human biomonitoring - Christoph Schmidtkunz; Katharina E. Ebert; Isabell Schönrath; Katja Küpper; Thomas Brüning; Holger M. Koch; Gabriele Leng (Toxicology Letters, 2026)

An arsenolipid accumulates in mouse brain following oral exposure - Georg Raber; Franziska Ebert; Michael Stiboller; Sandra M. Müller; Kevin A. Francesconi; Tanja Schwerdtle (Journal of Hazardous Materials, 2026)

Class switched bovine ultralong CDR H3 amplicons versus canonical in immune and non-immune tissues - Karina L. Hissen; Morgan Sheppard; Jeannine A. Ott; Kerstin K. Landrock; Casey Whitley; Nicholas Ebert; J. M. Cody Horton; Nicole A. Glenn; Yoonsung Jung; Vaughn V. Smider; Michael F. Criscitiello (Immunogenetics, 2026)
Within the bovine immune response, a distinct type of immunoglobulin (Ig), known as ultralong complementarity-determining region 3 (CDR3) antibodies, coexists alongside canonical Igs. These ultralong heavy chains (HC) feature a remarkable structure with a lengthened CDR3 of the heavy chain (CDR H3), allowing them to adopt either a smaller and more extended paratope than canonical antibodies. However, very little is known about the distribution of ultralong CDR H3s in cattle tissues and which isotypes they are ultimately associated with. This study analyzed and quantified the amplicons of the five immunoglobulin isotypes (IgM, IgD, IgG, IgA, and IgE) for both the canonical and ultralong CDR H3 throughout 24 Bos taurus tissues. IgH amplicons analysis identified an extensive repertoire of expressed canonical and ultralong CDR H3s of each isotype in most tissues. Ultralong cattle Igs were preferentially switched to the IgG isotype, especially in the medial retropharyngeal lymph node draining the immunization site. Additionally, B cells producing canonical Igs in bone marrow switched most to the IgG isotype. These data suggest that ultralong CDR H3 may be uniquely qualified to handle some antigens. A more comprehensive understanding of isotype and tissue-specific immune responses of these unusual antibodies can provide a deeper insight into their function within the overall cattle immune system, offering unique opportunities for innovations for in both bovine health and human immunotherapeutics.

Behaviour of the critical elements As, Bi, In, Sb, and Te during processing of a skarn ore: A case study of the Ruwai Zn-Pb-Ag Deposit, Central Kalimantan, Indonesia - Shelly M. Faizy; Doreen Ebert; Alkis Kontonikas-Charos; Mathias Burisch; Arifudin Idrus; Ernowo Ernowo; Anggara Widyastanto; Max Frenzel (Minerals Engineering, 2025)

Human metabolism and excretion kinetics of Bronopol after oral administration - Isabell Schönrath; Christoph Schmidtkunz; Katharina E. Ebert; Katja Küpper; Thomas Brüning; Holger M. Koch; Gabriele Leng (Archives of Toxicology, 2025)

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Crude glycerol as a sustainable source for carbon-based photoluminescent material - Amanda T. Vieira; Hevelyn V. Ebert; Eralci M. Therézio; Ailton J. Terezo; Ariane I. Barros; Adriano B. de Siqueira; Mario R.S. Soares (Biomass and Bioenergy, 2025)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Mechanistic in silico explorations of the immunogenic and synergistic effects of radiotherapy and immunotherapy: a critical review - Allison M. Ng; Kelly M. MacKinnon; Alistair A. Cook; Rebecca A. D’Alonzo; Pejman Rowshanfarzad; Anna K. Nowak; Suki Gill; Martin A. Ebert (Physical and Engineering Sciences in Medicine, 2024)
Immunotherapy is a rapidly evolving field, with many models attempting to describe its impact on the immune system, especially when paired with radiotherapy. Tumor response to this combination involves a complex spatiotemporal dynamic which makes either clinical or pre-clinical in vivo investigation across the resulting extensive solution space extremely difficult. In this review, several in silico models of the interaction between radiotherapy, immunotherapy, and the patient’s immune system are examined. The study included only mathematical models published in English that investigated the effects of radiotherapy on the immune system, or the effect of immuno-radiotherapy with immune checkpoint inhibitors. The findings indicate that treatment efficacy was predicted to improve when both radiotherapy and immunotherapy were administered, compared to radiotherapy or immunotherapy alone. However, the models do not agree on the optimal schedule and fractionation of radiotherapy and immunotherapy. This corresponds to relevant clinical trials, which report an improved treatment efficacy with combination therapy, however, the optimal scheduling varies between clinical trials. This discrepancy between the models can be attributed to the variation in model approach and the specific cancer types modeled, making the determination of the optimum general treatment schedule and model challenging. Further research needs to be conducted with similar data sets to evaluate the best model and treatment schedule for a specific cancer type and stage.

Nutrition Analysis and Advanced Artificial Intelligence (AI) Predicts Weight Loss for People with Type 2 Diabetes (T2D) - C. Brown; A. Iyer; A. Kumbara; M. Ebert (Journal of the Academy of Nutrition and Dietetics, 2024)

Differences in withdrawal symptoms, microglia activity, and cognitive functioning in rats exposed to continuous low-dose heroin in-utero - Sara L. Mills-Huffnagle; Charles N. Zawatsky; Gjhvona Bryant; Michael Ebert; Corinne M. Augusto; Ann Sipe; Nelli Horvath; Jennifer E. Nyland (Neurotoxicology and Teratology, 2024)

Human urinary excretion kinetics of the antimycotic climbazole: Biomonitoring of two new metabolites after oral and dermal dosage - Isabell Schönrath; Christoph Schmidtkunz; Katharina E. Ebert; Katja Küpper; Thomas Brüning; Holger M. Koch; Gabriele Leng (Toxicology Letters, 2024)

Harriotta avia sp. nov. – a new rhinochimaerid (Chimaeriformes: Rhinochimaeridae) described from the Southwest Pacific - Brittany Finucci; Dominique Didier; David A. Ebert; Madeline E. Green; Jenny M. Kemper (Environmental Biology of Fishes, 2024)

Toxicokinetics of homosalate in humans after dermal application: applicability of oral-route data for exposure assessment by human biomonitoring - Katharina E. Ebert; Peter Griem; Tobias Weiss; Thomas Brüning; Heiko Hayen; Holger M. Koch; Daniel Bury (Archives of Toxicology, 2024)
Homosalate (HMS) is a UV filter used in sunscreens and personal care products as a mixture of cis - and trans -isomers. Systemic absorption after sunscreen use has been demonstrated in humans, and concerns have been raised about possible endocrine activity of HMS, making a general population exposure assessment desirable. In a previous study, it was shown that the oral bioavailability of cis -HMS ( c HMS) is lower than that of trans -HMS ( t HMS) by a factor of 10, calling for a separate evaluation of both isomers in exposure and risk assessment. The aim of the current study is the investigation of HMS toxicokinetics after dermal exposure. Four volunteers applied a commercial sunscreen containing 10% HMS to their whole body under regular-use conditions (18–40 mg HMS (kg bw) −1 ). Parent HMS isomers and hydroxylated and carboxylic acid metabolites were quantified using authentic standards and isotope dilution analysis. Further metabolites were investigated semi-quantitatively. Elimination was delayed and slower compared to the oral route, and terminal elimination half-times were around 24 h. After dermal exposure, the bioavailability of c HMS was a factor of 2 lower than that of t HMS. However, metabolite ratios in relation to the respective parent isomer were very similar to the oral route, supporting the applicability of the oral-route urinary excretion fractions for dermal-route exposure assessments. Exemplary calculations of intake doses showed margins of safety between 11 and 92 (depending on the approach) after single whole-body sunscreen application. Human biomonitoring can reliably quantify oral and dermal HMS exposures and support the monitoring of exposure reduction measures.

A novel SARS-CoV-2 modified live vaccine with an optimized safety profile induces sterile immunity in Syrian hamsters - A. Breithaupt; T. Britzke; J. Schön; G.T. Barut; N.J. Halwe; L. Ulrich; N. Ebert; B. Trüeb; M. Brügger; V. Thiel; M. Beer; D. Hoffmann (Journal of Comparative Pathology, 2024)

The end of an entire biome? World's largest wetland, the Pantanal, is menaced by the Hidrovia project which is uncertain to sustainably support large-scale navigation - Karl M. Wantzen; Mario Luis Assine; Ieda Maria Bortolotto; Debora Fernandes Calheiros; Zilca Campos; Agostinho Carlos Catella; Rafael Morais Chiaravalotti; Walter Collischonn; Eduardo Guimarães Couto; Catia Nunes da Cunha; Geraldo Alves Damasceno-Junior; Carolina Joana da Silva; et al. (Science of The Total Environment, 2024)

Spatial extent and isolation of marine artificial structures mediate fish density - Virginia A. Gilliland; Avery E. Fessler; Avery B. Paxton; Erik F. Ebert; Ryan M. Tharp; Brendan J. Runde; Nathan M. Bacheler; Jeffrey A. Buckel; J. Christopher Taylor (Frontiers in Marine Science, 2023)
Installations of artificial structures in coastal oceans create de facto habitat for marine life. These structures encompass wide varieties of physical characteristics, reflecting their multiple, diverse purposes and creating a need to understand which characteristics maximize fish habitat. Here, we test how physical characteristics – horizontal area, vertical relief, and spatial isolation – relate to fish density from echosounder surveys over artificial structures like concrete pipes, train boxcars, and ships purposely sunk to function as reefs. Echosounder mapping of 31 artificial reef structures and associated fish across a 200 km linear length of the continental shelf of North Carolina, USA, revealed that structures with greater horizontal area and vertical relief host higher fish densities than smaller, shorter structures. Artificial structure spatial arrangement also relates to fish density, as isolated structures are generally associated with greater localized fish densities than structures closer to one another. Patterns in the relationships between fish density and reef characteristics differed for schooling fish, as there was some evidence that reefs of intermediate area exhibited higher schooling fish density. These results suggest that intentional design and spatial arrangement of marine built structures like artificial reefs relates to and can be deliberately incorporated into siting and deployment decisions to enhance their role as fish habitat.

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Combined synoptic and regional weather patterns affecting atmospheric Poaceae pollen concentrations in Sydney, Australia - Charlotte M. Waudby; Steven C. Sherwood; Nicholas J. Osborne; Paul J. Beggs; Jane Al-Kouba; Elizabeth E. Ebert; David J. Muscatello (Aerobiologia, 2022)
Inhalation of grass pollen can result in acute exacerbation of asthma, prompting questions about how grass pollen reaches metropolitan areas. We establish typical atmospheric Poaceae (grass) pollen concentrations recorded at two pollen samplers within the Sydney basin in eastern Australia and analyse their correlation with each other and meteorological variables. We determine the effect of synoptic and regional airflow on Poaceae pollen transport during a period of extreme (≥ 100 grains m −3 air) concentration and characterise the meteorology. Finally, we tested the hypothesis that most Poaceae pollen captured by the pollen samplers originated from local sources. Fifteen months of daily pollen data, three days of hourly atmospheric Poaceae pollen concentrations and fifteen months of hourly meteorology from two locations within the Sydney basin were used. Weather Research Forecasting (WRF), Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) modelling and conditional bivariate probability functions (CBPF) were used to assess Poaceae pollen transport. Most Poaceae pollen collected was estimated to be from local sources under low wind speeds. Extreme daily Poaceae pollen concentrations were rare, and there was no strong evidence to support long-distance Poaceae pollen transport into the Sydney basin or across the greater Sydney metropolitan area. Daily average pollen concentrations mask sudden increases in atmospheric Poaceae pollen, which may put a significant and sudden strain on the healthcare system. Mapping of Poaceae pollen sources within Sydney and accurate prediction of pollen concentrations are the first steps to an advanced warning system necessary to pre-empt the healthcare resources needed during pollen season.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Friend or foe? The role of biotic agents in drought-induced plant mortality - Robert J. Griffin-Nolan; Neha Mohanbabu; Sarah Araldi-Brondolo; Alexander R. Ebert; Julie LeVonne; Joanna I. Lumbsden-Pinto; Hannah Roden; Jordan R. Stark; Jordon Tourville; Katie M. Becklin; John E. Drake; Douglas A. Frank; et al. (Plant Ecology, 2021)

An Exploratory Study of Telomere Length in the Deep-Sea Shark, Etmopterus granulosus - Melissa C. Nehmens; Rebecca M. Varney; Alexis M. Janosik; David A. Ebert (Frontiers in Marine Science, 2021)
The history of elasmobranch ageing highlights the difficulty of age estimation in animals lacking ossified structures. Ageing techniques are numerous, yet all are limited by difficulties of validation and verification and inherent subjectivity. Sample scarcity further hinders progress as limited samples cannot be risked on exploratory techniques. This study explored the use of genetic analysis of telomeres as a method of age determination in a deep-sea shark, Etmopterus granulosus , a representative of a poorly studied taxon with regard to ageing due to sample scarcity. Telomeres were amplified in 39 individuals with qPCR, compared across samples, and were found to differ across size classes. More work is needed to determine whether telomeres consistently correlate with size class across elasmobranchs. However, telomeres offer easily obtainable data that can be combined with traditional methods to provide additional points of comparison for elasmobranch biology. Our results underscore the importance of expanding current ageing methods and highlight a necessary distinction between chronological and biological ages when describing elasmobranch populations.

Ghosts of the deep – Biodiversity, fisheries, and extinction risk of ghost sharks - Brittany Finucci; Jessica Cheok; David A. Ebert; Katelyn Herman; Peter M. Kyne; Nicholas K. Dulvy (Fish and Fisheries, 2021)
Ghost sharks (subclass Holocephali) remain a largely data‐poor group of cartilaginous fishes. The general paucity of attention may partially be related to identification and unresolved taxonomic issues, occurrence in the deep oceans, and their low value and interest in fisheries (which some notable exceptions). Here, we synthesize and assess the extinction risk of all known extant ghost sharks (52 species) by applying the IUCN Red List of Threatened Species Categories and Criteria. Ghost sharks have a low proportion of threatened (8%) and Near Threatened (8%) species, with most species (69%) assessed as Least Concern. The group still exhibits some data deficiency (15%), and biological information is lacking for most species. Endemism is high, with 37% of species known from only one location or one country. Species richness was highest in the Northeast Atlantic, off the northwest coast of Africa (Morocco to Mauritania), the East China Sea, New Zealand and off the northwest coast of South America (Ecuador and Peru). Ghost sharks are predominately taken as by‐catch, but some targeted fishing and/or retention for the liver oil trade occurs. Species‐specific reporting, monitoring and management are required to assess population trends, and further investigation is needed on trade and use, particularly for higher risk species including the sicklefin chimaeras (genus Neoharriotta ) and the American Elephantfish ( Callorhynchus callorhynchus , Callorhinidae).

DeepSurvNet: deep survival convolutional network for brain cancer survival rate classification based on histopathological images - Amin Zadeh Shirazi; Eric Fornaciari; Narjes Sadat Bagherian; Lisa M. Ebert; Barbara Koszyca; Guillermo A. Gomez (Medical & Biological Engineering & Computing, 2020)
Histopathological whole slide images of haematoxylin and eosin (H&E)-stained biopsies contain valuable information with relation to cancer disease and its clinical outcomes. Still, there are no highly accurate automated methods to correlate histolopathological images with brain cancer patients’ survival, which can help in scheduling patients therapeutic treatment and allocate time for preclinical studies to guide personalized treatments. We now propose a new classifier, namely, DeepSurvNet powered by deep convolutional neural networks, to accurately classify in 4 classes brain cancer patients’ survival rate based on histopathological images (class I, 0–6 months; class II, 6–12 months; class III, 12–24 months; and class IV, >24 months survival after diagnosis). After training and testing of DeepSurvNet model on a public brain cancer dataset, The Cancer Genome Atlas, we have generalized it using independent testing on unseen samples. Using DeepSurvNet, we obtained precisions of 0.99 and 0.8 in the testing phases on the mentioned datasets, respectively, which shows DeepSurvNet is a reliable classifier for brain cancer patients’ survival rate classification based on histopathological images. Finally, analysis of the frequency of mutations revealed differences in terms of frequency and type of genes associated to each class, supporting the idea of a different genetic fingerprint associated to patient survival. We conclude that DeepSurvNet constitutes a new artificial intelligence tool to assess the survival rate in brain cancer.

Correction to: Redescription of the bigeye chimaera, Hydrolagus macrophthalmus de Buen, 1959 (Chondrichthyes: Chimaeriformes), with a genetic characterization of the species - Matthew Jew; David A. Ebert; Jenny M. Kemper; Kristin Walovich; Kimberly L. Quaranta (Marine Biodiversity, 2019)

Redescription of the bigeye chimaera, Hydrolagus macrophthalmus de Buen, 1959 (Chondrichthyes: Chimaeriformes), with a genetic characterization of the species - Matthew Jew; David A. Ebert; Jenny M. Kemper; Kristin Walovich; Kimberly L. Quaranta (Marine Biodiversity, 2019)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Arsenic-containing hydrocarbons: effects on gene expression, epigenetics, and biotransformation in HepG2 cells - S. M. Müller; H. Finke; F. Ebert; J. F. Kopp; F. Schumacher; B. Kleuser; K. A. Francesconi; G. Raber; T. Schwerdtle (Archives of Toxicology, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Effects of arsenolipids on in vitro blood-brain barrier model - S. M. Müller; F. Ebert; G. Raber; S. Meyer; J. Bornhorst; S. Hüwel; H.-J. Galla; K. A. Francesconi; T. Schwerdtle (Archives of Toxicology, 2018)

Squalus bassi sp. nov., a new long‐snouted spurdog (Chondrichthyes: Squaliformes: Squalidae) from the Agulhas Bank - S. T. de. F. L. Viana; M. R. de Carvalho; D. A. Ebert (Journal of Fish Biology, 2017)
The long‐snouted African spurdog Squalus bassi sp. nov. is described based on material collected from the outer shelf and upper continental slope off South Africa and Mozambique. Squalus bassi shares with S. mitsukurii, S. montalbani, S. chloroculus, S. grahami , S. griffini, S. edmundsi , S. quasimodo and S. lobularis a large snout with prenarial length greater than distance between nostrils and upper labial furrows, dermal denticles tricuspidate and rhomboid and elevated number of vertebrae. Squalus bassi can be distinguished from all its congeners by a combination of body and fin colouration, external morphometrics, vertebral counts and shape of dermal denticles. Similar long‐snouted congeners from the Indo‐Pacific region, including S. montalbani , S. edmundsi and S. lalannei are compared in detail with the new species. This new species has been misidentified as the Japanese S. mitsukurii and the Mediterranean S. blainvillei due to the lack of comparative morphological analyses. The validity of the nominal species S. mitsukurii in the south‐eastern Atlantic Ocean and western Indian Ocean is also clarified herein, indicating it has a more restricted geographical distribution in the North Pacific Ocean.

Sympatric walleye Sander vitreus and sauger Sander canadensis in large reservoirs: Variable isotopic niche size and overlap across multiple time scales - J. C. Butt; R. L. Eberts; C. M. Somers (Fisheries Management and Ecology, 2017)
Walleye Sander vitreus (Mitchill) and sauger Sander canadensis (Griffith & Smith) may occupy similar niches in sympatric populations, but their long‐term resource use is poorly studied. Multi‐tissue (liver, muscle and bone) isotopic niche analyses were used to compare resource use by these species in two large reservoirs in Saskatchewan, Canada. Population isotopic niches were larger for sauger (1.73‰ 2 –3.60‰ 2 ) than walleye (0.51‰ 2 –2.61‰ 2 ) in Lake Diefenbaker, but opposite in Tobin Lake (sauger = 0.54‰ 2 –2.57‰ 2 ; walleye = 1.30‰ 2 –2.94‰ 2 ). Analyses of population overlap suggest that these species co‐exist via niche partitioning, but partitioning was more pronounced in Lake Diefenbaker (overlap = 6%–38%; Tobin Lake overlap = 18%–62%). The size of individual niches and levels of intra‐ and interspecific overlap among individual fish also varied with reservoir. This study shows that walleye and sauger use different resources across different time scales, but the degree of partitioning can vary markedly with environment.

Dietary variability in two common Alaskan skates (Bathyraja interrupta and Raja rhina) - Jenny M. Kemper; Joseph J. Bizzarro; David A. Ebert (Marine Biology, 2017)

Comparative age and growth of the Aleutian skate, Bathyraja aleutica, from the eastern Bering Sea and Gulf of Alaska - Diane L. Haas; David A. Ebert; Gregor M. Cailliet (Environmental Biology of Fishes, 2016)

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

Model-based reasoning to foster environmental and socio-scientific literacy in higher education - Amanda E. Sorensen; Rebecca C. Jordan; Rachel Shwom; Diane Ebert-May; Cindy Isenhour; Aaron M. McCright; Jennifer Meta Robinson (Journal of Environmental Studies and Sciences, 2016)

Effects of three novel resistant black raspberry selections on Amphorophora agathonica feeding behavior and performance - D. Lightle; M. Dossett; T. Ebert; C. E. Finn; R. R. Martin; J. C. Lee (Arthropod-Plant Interactions, 2015)

High Resolution HIRLAM Simulations of the Role of Low-Level Sea-Breeze Convergence in Initiating Deep Moist Convection in the Eastern Iberian Peninsula - Cesar Azorin-Molina; Sander Tijm; Elizabeth E. Ebert; Sergio-M. Vicente-Serrano; Maria-Jose Estrela (Boundary-Layer Meteorology, 2015)

Reproduction of the sandpaper skate, Bathyraja kincaidii (Garman 1908) in the eastern North Pacific - Colleena R. Perez-Brazen; Gregor M. Cailliet; David A. Ebert (Environmental Biology of Fishes, 2014)

Fusobacterium nucleatum associates with stages of colorectal neoplasia development, colorectal cancer and disease outcome - L. Flanagan; J. Schmid; M. Ebert; P. Soucek; T. Kunicka; V. Liska; J. Bruha; P. Neary; N. Dezeeuw; M. Tommasino; M. Jenab; J. H. M. Prehn; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Age and growth characteristics of the Starry Skate, Raja stellulata, with a description of life history and habitat trends of the central California, U.S.A., skate assemblage - Kelsey C. James; David A. Ebert; Lisa J. Natanson; Gregor M. Cailliet (Environmental Biology of Fishes, 2014)

Half a century (1954–2009) of dissection data of sea urchins from the North American Pacific coast (Mexico–Canada) - T. A. Ebert; J. C. Hernández; S. Clemente; M. P. Russell; L. V. Basch; R. A. Boolootian; P. M. Detwiler; M. C. Kenner; A. L. Lawrence; J. M. Lawrence; D. L. Leighton; J. S. Palleiro; et al. (Ecology, 2013)
Total body size, mass or linear measurements, and gonad mass or volumes have been recorded for the North American Pacific coast sea urchins Strongylocentrotus purpuratus, Mesocentrotus (Strongylocentrotus) franciscanus, and Lytechinus pictus by various workers at diverse sites and for varying lengths of time from 1954 to 2009. Some dissections included other body components such as the gut, body wall, and Aristotle's lantern, and some dissections included both wet and dry mass. There are numerous peer‐reviewed publications that have used some of these data, but some data have appeared only in graduate theses or in the gray literature. There also are data that have never appeared outside the original data sheets. Historically, data were used to describe reproductive cycles and then to compare responses to stressors such as food limitation or pollution. Differences in temperature among sites also have been explored. More recently, dissection data have linked gonad development to ocean conditions, so called bottom‐up forcing. The data set presented here is a historical record of gonad development for a common group of marine invertebrates in intertidal and nearshore environments, which can be used to test hypotheses concerning future changes associated with climate change and ocean acidification along the Pacific Coast of North America.

Development of best practices for ex situ conservation of radish germplasm in the context of the crop genebank knowledge base - I. Thormann; Q. Yang; C. Allender; N. Bas; G. Campbell; M. E. Dulloo; A. W. Ebert; U. Lohwasser; C. Pandey; L. D. Robertson; O. Spellman (Genetic Resources and Crop Evolution, 2013)

Predators of juvenile sea urchins and the effect of habitat refuges - S. Clemente; J. C. Hernández; G. Montaño-Moctezuma; M. P. Russell; T. A. Ebert (Marine Biology, 2013)

Proteomic analysis of the Cyanophora paradoxa muroplast provides clues on early events in plastid endosymbiosis - Fabio Facchinelli; Mathias Pribil; Ulrike Oster; Nina J. Ebert; Debashish Bhattacharya; Dario Leister; Andreas P. M. Weber (Planta, 2013)

Parameters determining the efficacy of adoptive CD8 T-cell therapy of cytomegalovirus infection - Stefan Ebert; Jürgen Podlech; Dorothea Gillert-Marien; Kerstin M. Gergely; Julia K. Büttner; Annette Fink; Kirsten Freitag; Doris Thomas; Matthias J. Reddehase; Rafaela Holtappels (Medical Microbiology and Immunology, 2012)

Breaking with tradition: redefining measures for diet description with a case study of the Aleutian skate Bathyraja aleutica (Gilbert 1896) - Simon C. Brown; Joseph J. Bizzarro; Gregor M. Cailliet; David A. Ebert (Environmental Biology of Fishes, 2012)

Evidence of stability in a chondrichthyan population: case study of the spotted ratfish Hydrolagus colliei (Chondrichthyes: Chimaeridae) - L. A. K. Barnett; D. A. Ebert; G. M. Cailliet (Journal of Fish Biology, 2012)
Results presented here provide evidence of an exception to the generalization that all chondrichthyan populations are especially vulnerable to exploitation to the extent that they remain at low abundance for a protracted or indefinite duration even after exploitation rates are reduced. Delta log‐normal generalized linear models (GLM) and cluster analysis of fishery‐independent catch‐per‐unit‐effort (CPUE) data from 1977 to 2006 indicated the presence of at least two distinct stocks of spotted ratfish Hydrolagus colliei off the U.S. West Coast. CPUE of the continental slope and northern continental shelf and upper slope populations did not vary between 1977 and 1995 and increased from 1995 to 2006. On the basis of the timing of these changes, it is likely that both fishing and climate influenced these trends. Sex and size‐specific differences in bathymetric distribution, along with the identification of nursery sites, indicate that fishery by‐catch could have a significant effect on population growth. These aggregative behaviours, combined with low fecundity, indicate that H. colliei may be vulnerable to irreversible population depletion by fisheries mortality. Temporal abundance trends indicated, however, that their population size has increased significantly within the last decade, a demonstration of population stability. A literature review indicated that there is also evidence for population stability in other chondrichthyans. The paradigm that all chondrichthyan populations fail to rebuild in response to exploitation, therefore, may not be as broadly applicable as previously thought. Thus, it is not necessarily sufficient to make generalizations regarding the vulnerability of chondrichthyans across higher taxonomic scales.

Stable‐isotope analysis of a deep‐sea benthic‐fish assemblage: evidence of an enriched benthic food web - M. D. Boyle; D. A. Ebert; G. M. Cailliet (Journal of Fish Biology, 2012)
In this study, fishes and invertebrates collected from the continental slope (1000 m) of the eastern North Pacific Ocean were analysed using stable‐isotope analysis (SIA). Resulting trophic positions ( T P ) were compared to known diets and habitats from the literature. Dual isotope plots indicated that most species groups (invertebrates and fishes) sorted as expected along the carbon and nitrogen axes, with less intraspecific variability than interspecific variability. Results also indicated an isotopically distinct benthic and pelagic food web, as the benthic food web was more enriched in both nitrogen and carbon isotopes. Trophic positions from SIA supported this finding, resulting in the assignment of fishes to different trophic positions from those expected based on published dietary information. These differences can be explained largely by the habitat of the prey and the percentage of the diet that was scavenged. A mixing model estimated dietary contributions of prey similar to those of the known diet of Bathyraja trachura from stomach‐content analysis (SCA). Linear regressions indicated that trophic positions calculated from SIA and SCA, when plotted against B. trachura total length for 32 individuals, exhibited similar variation and patterns. Only the T P from SCA yielded significant results (stomach content: P P > 0·05).

An overview on the role of Hexanchiformes in marine ecosystems: biology, ecology and conservation status of a primitive order of modern sharks - A. Barnett; J. M. Braccini; C. A. Awruch; D. A. Ebert (Journal of Fish Biology, 2012)
The large size, high trophic level and wide distribution of Hexanchiformes (cow and frilled sharks) should position this order as important apex predators in coastal and deep‐water ecosystems. This review synthesizes available information on Hexanchiformes, including information not yet published, with the purpose of evaluating their conservation status and assessing their ecological roles in the dynamics of marine ecosystems. Comprising six species, this group has a wide global distribution, with members occurring from shallow coastal areas to depths of c. 2500 m. The limited information available on their reproductive biology suggests that they could be vulnerable to overexploitation ( e.g. small litter sizes for most species and suspected long gestation periods). Most of the fishing pressure exerted on Hexanchiformes is in the form of commercial by‐catch or recreational fishing. Comprehensive stock and impact assessments are unavailable for most species in most regions due to limited information on life history and catch and abundance time series. When hexanchiform species have been commercially harvested, however, they have been unable to sustain targeted fisheries for long periods. The potentially high vulnerability to intense fishing pressure warrants a conservative exploitation of this order until thorough quantitative assessments are conducted. At least some species have been shown to be significant apex predators in the systems they inhabit. Should Hexanchiformes be removed from coastal and deep‐water systems, the lack of sympatric shark species that share the same resources suggests no other species would be capable of fulfilling their apex predator role in the short term. This has potential ecosystem consequences such as meso‐predator release or trophic cascades. This review proposes some hypotheses on the ecology of Hexanchiformes and their role in ecosystem dynamics, highlighting the areas where critical information is required to stimulate research directions.

Comparison of particle-tracking and lumped-parameter age-distribution models for evaluating vulnerability of production wells to contamination - S. M. Eberts; J. K. Böhlke; L. J. Kauffman; B. C. Jurgens (Hydrogeology Journal, 2012)

Problems of the gonad index and what can be done: analysis of the purple sea urchin Strongylocentrotus purpuratus - T. A. Ebert; J. C. Hernandez; M. P. Russell (Marine Biology, 2011)

Depth-dependent sampling to identify short-circuit pathways to public-supply wells in multiple aquifer settings in the United States - Matthew K. Landon; Bryant C. Jurgens; Brian G. Katz; Sandra M. Eberts; Karen R. Burow; Christy A. Crandall (Hydrogeology Journal, 2010)

Assessment of the dorsal fin spine for chimaeroid (Holocephali: Chimaeriformes) age estimation - L. A. K. Barnett; D. A. Ebert; G. M. Cailliet (Journal of Fish Biology, 2009)
Previous attempts to age chimaeroids have not rigorously tested assumptions of dorsal fin spine growth dynamics. Here, novel imaging and data‐analysis techniques revealed that the dorsal fin spine of the spotted ratfish Hydrolagus colliei is an unreliable structure for age estimation. Variation among individuals in the relationship between spine width and distance from the spine tip indicated that the technique of transverse sectioning may impart imprecision and bias to age estimates. The number of growth‐band pairs observed by light microscopy in the inner dentine layer was not a good predictor of body size. Mineral density gradients, indicative of growth zones, were absent in the dorsal fin spine of H. colliei , decreasing the likelihood that the bands observed by light microscopy represent a record of growth with consistent periodicity. These results indicate that the hypothesis of aseasonal growth remains plausible and it should not be assumed that chimaeroid age is quantifiable by standard techniques.

A map of human impacts to a “pristine” coral reef ecosystem, the Papahānaumokuākea Marine National Monument - K. A. Selkoe; B. S. Halpern; C. M. Ebert; E. C. Franklin; E. R. Selig; K. S. Casey; J. Bruno; R. J. Toonen (Coral Reefs, 2009)

Maturity, fecundity, and reproductive cycle of the spotted ratfish, Hydrolagus colliei - Lewis A. K. Barnett; Ryan L. Earley; David A. Ebert; Gregor M. Cailliet (Marine Biology, 2009)

Level ground and uphill cycling ability in elite female mountain bikers and road cyclists - F. M. Impellizzeri; T. Ebert; A. Sassi; P. Menaspà; E. Rampinini; D. T. Martin (European Journal of Applied Physiology, 2007)

Influence of mineral precipitation on the performance and long-term stability of Fe 0 -permeable reactive barriers: A review on the basis of 19 Fe 0 -reactive barrier sites - A. Parbs; M. Ebert; A. Dahmke (Grundwasser, 2007)

Reproductive biology of deep-sea catsharks (Chondrichthyes: Scyliorhinidae) in the eastern North Pacific - Brooke E. Flammang; David A. Ebert; Gregor M. Cailliet (Environmental Biology of Fishes, 2007)

Age and growth of the roughtail skate Bathyraja trachura (Gilbert 1892) from the eastern North Pacific - Chanté D. Davis; Gregor M. Cailliet; David A. Ebert (Environmental Biology of Fishes, 2007)

Food habits of the longnose skate, Raja rhina (Jordan and Gilbert, 1880), in central California waters - Heather J. Robinson; Gregor M. Cailliet; David A. Ebert (Environmental Biology of Fishes, 2007)

Food habits of the sandpaper skate, Bathyraja kincaidii (Garman, 1908) off central California: seasonal variation in diet linked to oceanographic conditions - Christopher S. Rinewalt; David A. Ebert; Gregor M. Cailliet (Environmental Biology of Fishes, 2007)

Centres of Crop Diversity and/or Origin, Genetically Modified Crops and Implications for Plant Genetic Resources Conservation - J. M. M. Engels; A. W. Ebert; I. Thormann; M. C. de Vicente (Genetic Resources and Crop Evolution, 2006)

Das Produkt Kaviar und der histologische Nachweis seiner Verfälschung - M. Ebert; R. Islam (Journal of Consumer Protection and Food Safety, 2006)

Galantamine: a cholinergic patch in the treatment of alcoholism: a randomized, placebo-controlled trial - K. Mann; K. Ackermann; A. Diehl; D. Ebert; G. Mundle; H. Nakovics; T. Reker; G. Richter; L. G. Schmidt; M. Driessen; K. Rettig; K. Opitz; et al. (Psychopharmacology, 2006)

Linking Land Cover and Water Quality in New York City’S Water Supply Watersheds - M. H. Mehaffey; M. S. Nash; T. G. Wade; D. W. Ebert; K. B. Jones; A. Rager (Environmental Monitoring and Assessment, 2005)

Stocking impact and migration pattern in an anadromous brown trout ( Salmo trutta ) complex: where have all the stocked spawning sea trout gone? - Daniel E. Ruzzante; Michael M. Hansen; Dorte Meldrup; Kaare M. Ebert (Molecular Ecology, 2004)
We examined polymorphism at seven microsatellite loci among sea trout ( Salmo trutta ) ( n = 846) collected from three areas in the Limfjord (Denmark). We then assessed their potential population source by comparing, using a mixed stock analysis (MSA) Bayesian framework, their genetic composition to that of brown trout collected from 32 tributaries pooled into nine geographical regions ( n = 3801) and two hatcheries ( n = 222) used for stocking. For each of the three regional sea trout groups (western, central and eastern Limfjord, n = 91, n = 426, n = 329, respectively), MSA was conducted with (i) all individuals in the group, (ii) with the subset of spawning sea trout only and (iii) with the subset of foraging, nonspawning individuals only, a subset that consisted primarily of sea trout caught during their first year at sea. For all three regional sea trout groups, a higher proportion of individuals (regardless of whether they were foraging or spawning) appear to have originated from the rivers that drain locally, than from the rivers that drain in other parts of the Limfjord. This suggests (1) that sea trout, at least during their first year at sea, undertake limited migrations within the Limfjord system and (2) that sea trout on their spawning run were caught close to their natal rivers. The proportion of sea trout of hatchery origin varied widely among all three Limfjord areas and broadly reflected regional stocking histories, with high proportions of sea trout of domestic origin in the east (39.3%), where stocking with domestic trout was practised intensely at the time of sampling, and in the west (57.2%), where a programme of coastal stocking of post smolts took place over several years in the early 1990s. In contrast, in the central Limfjord, where stocking with domestic trout was largely abandoned in the early 1990s, the proportion of sea trout of domestic origin was only 8.5%. Interestingly, for all three regional sea trout groups, virtually no sea trout of hatchery origin were found among the spawning individuals, which were on average larger than the nonspawning sea trout. These results suggest that stocked domestic brown trout that become anadromous experience high mortality at sea and are therefore largely absent among the larger, spawning individuals. We conclude that sea trout of domestic origin exhibit much reduced ability to reproduce and are unlikely to contribute significantly to the local gene pool largely because of a relatively high mortality at sea before the onset of maturity.

Promoters for pregenomic RNA of banana streak badnavirus are active for transgene expression in monocot and dicot plants - Peer M. Schenk; Tony Remans; László Sági; Adrian R. Elliott; Ralf G. Dietzgen; Rony Swennen; Paul R. Ebert; Christopher P.L. Grof; John M. Manners (Plant Molecular Biology, 2001)

Effect of creatine supplementation on metabolism and performance in humans during intermittent sprint cycling - J. P. Finn; T. R. Ebert; R. T. Withers; M. F. Carey; M. Mackay; J. W. Phillips; M. A. Febbraio (European Journal of Applied Physiology, 2001)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Abundance, distribution, morphometrics, reproduction and diet of the Izak catshark - A. J. Richardson; G. Maharaj; L. J. V. Compagno; R. W. Leslie; D. A. Ebert; M. J. Gibbons (Journal of Fish Biology, 2000)
Holohalaelurus regani was caught in 38% of the 3314 bottom trawls conducted during routine demersal surveys o. the South African west and south coasts from 1986 to 1999. An index of biomass for H. regani has increased on the west coast, from 1606 t in 1986–1993 to 3012 t in 1994–1999, despite c. 130 t being taken annually as by–catch in the demersal fishery. On the south coast, there has also been an increase over the same period, from 793 to 1350 t. Females and juveniles were generally found in shallower water ( H. regani become mature at 450–500 mm LT, whereas females become mature at 400–450 mm LT. There is reproductive activity throughout the year and fecundity appears to be high. This species is a generalist feeder, with the diet comprising teleosts, crustaceans and cephalopods. H. regani also scavenges offal opportunistically. Its high fecundity, the relative protection of females and juveniles in shallow water that is rarely trawled, its opportunistic diet and its robust nature that may allow it to survive after it has been discarded, have enabled H. regani to increase in numbers, despite indirect fishing pressure.

Regional impact analysis of climate change on natural and managed forests in the Federal State of Brandenburg, Germany - P. Lasch; M. Lindner; B. Ebert; M. Flechsig; F.-W. Gerstengarbe; F. Suckow; P.C. Werner (Environmental Modeling & Assessment, 1999)

Dilatory effects of phosphodiesterase inhibitors on human hand veins in vivo - M. Grossmann; J. Braune; Ulrike Ebert; W. Kirch (European Journal of Clinical Pharmacology, 1998)

Effects of bis(tri-n-butyltin)oxide in Japanese quail exposed during egg laying period: An interlaboratory comparison study - Bert Schlatterer; Theodora M. M. Coenen; Eugen Ebert; Raimund Grau; Volker Hilbig; Reinhart Munk (Archives of Environmental Contamination and Toxicology, 1993)

Untersuchungen zu Struktur und Biogenese des sauren Polysaccharids von Penicillium islandicum (Islandinsure) - E. Ebert; M. H. Zenk (Archives of Microbiology, 1966)